2022
DOI: 10.1186/s12905-022-01962-0
|View full text |Cite
|
Sign up to set email alerts
|

How, when and where? A systematic review on abortion decision making in legally restricted settings in sub-Saharan Africa, Latin America, and the Caribbean

Abstract: Background With increasing global availability of medication abortion drugs, a safer option exists for many women to terminate a pregnancy even in legally restrictive settings. However, more than 22,000 women die each year from unsafe abortion, most often in developing countries where abortion is highly legally restricted. We conducted a systematic review to compile existing evidence regarding factors that influence women’s abortion-related decision making in countries where abortion is highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 78 publications
(301 reference statements)
2
7
0
Order By: Relevance
“…One of the ways women seek information while avoiding public exposure is to involve their partners who do not face the same risk of social shame. As suggested in other studies conducted in legally restricted abortion settings [ 12 , 28 ], we found male partners take on much responsibility in women’s abortion trajectories, often connecting their pregnant partners directly to healthcare providers. However, in doing so, our results indicate some partners infringed on women’s reproductive autonomy, making decisions without sharing information.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…One of the ways women seek information while avoiding public exposure is to involve their partners who do not face the same risk of social shame. As suggested in other studies conducted in legally restricted abortion settings [ 12 , 28 ], we found male partners take on much responsibility in women’s abortion trajectories, often connecting their pregnant partners directly to healthcare providers. However, in doing so, our results indicate some partners infringed on women’s reproductive autonomy, making decisions without sharing information.…”
Section: Discussionsupporting
confidence: 68%
“…Understanding how women obtain information about where to access abortion in a setting characterized by limited abortion-related knowledge and access to care is essential in reducing morbidity and mortality due to unsafe abortion. Lack of knowledge about abortion methods and sources, which often depends on an individual’s residence, age, and education, presents an initial obstacle to accessing safe abortion care [ 12 ]. This extends to knowledge of medication abortion specifically, which has been found to be higher among younger women [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While these explanations are plausible, it is also significant that after adjusting for confounding factors, this relationship was not significant; instead, the prevalence of depression in women in this age group was associated with lower levels of gender development and higher rates of intimate partner violence. Therefore, the most likely conclusion is that the link between abortion access and depression in older women of childbearing age is indirect, and is more directly related to women’s rights and social status in both the personal and political spheres [ 58 , 59 ]. This is supported by the additional analyses presented in this study, which show that abortion access is strongly and negatively associated with measures of gender inequality and intimate partner violence, and positively associated with a measure of gender development.…”
Section: Discussionmentioning
confidence: 99%
“…Even though some apps might include abortion as a topic no SRH-app could be identified that focused on abortion care. As an SRH issue with a high mortality, health apps dealing with said topic could be a potential aid when it comes to the decision-making process or to reducing the stigma still attached to abortion [93,94]. Social-structural factors were rarely the primary aim of the apps although they are highly relevant for the way we deal with SRH [20].…”
Section: Contents Of Srh Appsmentioning
confidence: 99%